(untitled) (Ustozlar uchun, 2025)
This paper explores the transformative role of digitalization and artificial intelligence (AI) in psychology and psychotherapy. Digital technologies, including online assessments, virtual reality, AI-driven chatbots, and machine learning algorithms, have revolutionized mental health diagnostics, treatment, and research. AI enhances personalization, efficiency, and accessibility of therapy while enabling data-driven insights into human behavior, cognition, and emotion. Virtual reality and digital monitoring tools facilitate preventive care and innovative therapeutic interventions. Despite numerous advantages, challenges such as privacy, ethical concerns, quality validation, and digital divide must be addressed. Overall, the integration of AI and digital tools is reshaping psychology, providing new opportunities for improving mental health care and evidence-based practice.